Copywriting and Rewriting in Digital Media: Professional Differences and Ethical Issues - Amangeldiyeva, G.S.; Abikeyeva, N.M.; Yertassova, G.K. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
This article examines copywriting and rewriting as professional practices in the digital media landscape, emphasizing their functional distinctions, methodological attributes, and ethical considerations. The study examines the historical evolution of copywriting, the transformation of textual production in the context of social media and digital platforms, and the growing role of rewriting in contemporary content markets. Using qualitative analysis, comparative methods, and normative evaluation, the research identifies key distinctions between original authorial writing and text transformation based on existing sources. The findings demonstrate that copywriting functions as a strategic and creative form of persuasive communication, whereas rewriting primarily serves adaptive and technical purposes related to content accessibility and optimization. At the same time, professional rewriting requires a high level of language skill and goes beyond just changing the text. Special attention is given to ethical challenges associated with rewriting practices, including issues of authorship, content duplication, misleading advertising, and the use of artificial intelligence in text generation. The results contribute to clarifying professional boundaries between copywriting and rewriting and emphasize the importance of ethical standards and transparency in digital communication.